Estimation of relationship between psychosocial stress and periodontal status using serum cortisol level: A clinico-biochemical study - Sunil Goyal; Siddhant Jajoo; G Nagappa; Gururaja Rao (Wolters Kluwer Medknow Publications, 2011)
Aims and Objectives: Psychological conditions, particularly psychosocial stress, have been implicated as risk indicators for periodontal disease. The aim of the present study was to explore the role of psychosocial stress that influences the periodontium with the use of a questionnaire data and serum cortisol level. Materials and Methods: In this study 47 subjects, both male and female, were taken and divided into two groups. Group I comprised of 16 chronic periodontitis subjects. Their stress level was evaluated using a standard questionnaire method (social readjustment rating scale). Plaque index (PI), gingival index (GI), periodontal disease index (PDI) and serum cortisol level were also measured. Group II comprised of 31 stressed subjects and their clinical parameters PI, GI, PDI and cortisol level were recorded. Statistical Analysis Used: Spearman's rank correlation coefficient and unpaired 't' test. Results: In group I statistically significant correlation (P<0.05) was found between cortisol and PDI; and cortisol and PI. In group II positive correlation was found between stress, cortisol, PI, GI and PDI. A statistically significant correlation was found between cortisol and smoking. Conclusion: Stress may be a contributing factor in periodontal disease.